If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + 2g = 4g + 0 Reorder the terms: 18 + 2g = 0 + 4g Remove the zero: 18 + 2g = 4g Solving 18 + 2g = 4g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-4g' to each side of the equation. 18 + 2g + -4g = 4g + -4g Combine like terms: 2g + -4g = -2g 18 + -2g = 4g + -4g Combine like terms: 4g + -4g = 0 18 + -2g = 0 Add '-18' to each side of the equation. 18 + -18 + -2g = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -2g = 0 + -18 -2g = 0 + -18 Combine like terms: 0 + -18 = -18 -2g = -18 Divide each side by '-2'. g = 9 Simplifying g = 9
| 5/9=m+1 | | d+9=113/12 | | 6+w=13/2 | | 5/6b=-5 | | w/3=6/7 | | 4/5+w=-6/5 | | 2y+27=5y+0 | | -7=k+4 | | m+2=4 | | b/5=7 | | 7t=35 | | 83/56=n+6/7 | | 5/9=d-4/9 | | a+18=7a+0 | | k-2/9=26/45 | | t+4=22/5 | | 7+m=84/11 | | a+2/5=7/5 | | w/-4=-2/3 | | 1+t=13/9 | | m+4=22/7 | | -6+w=-12 | | x+7/10=27/110 | | n/6=5/6 | | -5/9+k=-68/9 | | t-3=-32/9 | | w+1=-7 | | 5/9+x=-58/9 | | 7+w=31/4 | | -1/2w=-7/2 | | n+10=16 | | -5/6b=1/2 |